2019
DOI: 10.1155/2019/3546258
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effects of Paeonia Extract Mixture HT074 against Experimental Gastric Ulcers in Rats

Abstract: Background. Paeonia extract mixture HT074 is a standardized multiherbal mixture comprising extracts from Inula britannica flowers and Paeonia lactiflora roots, which are used to treat digestive disorders in traditional Korean medicine. This study was focused on elucidating the underlying mechanisms of the gastroprotective effects of HT074 in different gastric ulcer models. Methods. Gastric lesions were induced in rats by an HCl/EtOH solution, water immersion-restraint stress (WIRS), and indomethacin. Gastric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 73 publications
1
13
0
1
Order By: Relevance
“…To investigate the protective effect of LZD on gastrointestinal tract, a IND-induced duodenal ulcer model in rats was established, which is commonly and classically used in the search for gastroprotective natural medicines [27,28]. IND causes the duodenal damage by suppressing the prostaglandin biosynthesis, decreasing the mucus production, and reducing the blood circulation within the mucosa [29,30]. Acute exposure of the duodenal mucosa of rats to IND results in severe lesions similar to those emerging in patients with duodenal ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the protective effect of LZD on gastrointestinal tract, a IND-induced duodenal ulcer model in rats was established, which is commonly and classically used in the search for gastroprotective natural medicines [27,28]. IND causes the duodenal damage by suppressing the prostaglandin biosynthesis, decreasing the mucus production, and reducing the blood circulation within the mucosa [29,30]. Acute exposure of the duodenal mucosa of rats to IND results in severe lesions similar to those emerging in patients with duodenal ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Kim YS et al used the various agents inducing ulcersethanol/hydrochloric acid, NSAIDs, acute stress (water immersion-restraint stress-induced gastric lesion) to elucidate the effect of phenols of plant origin (paeoniflorin, albiflorin and paeonol). The authors concluded that plant phenolic compounds work primarily by increasing the secretion of prostaglandin-related mucus formation as the first line of defence, in the absence of a consistent anti-secretory effect, as in our case [28]. The involvement of prostaglandins as substances promoting mucus formation was highlighted by these authors by assessment of the reduction in death induced by indomethacin in AGS cells (human epithelial gastric cell line); at the same time, a gastroprotective effect dependent on endogenous sulfhydryl groups was observed, but independent of the formation of nitric oxide (NO) via NO-synthetase, a mechanism attributed to plant polyphenols by other researchers [18].…”
Section: Representative Images Of Ulcers and Associated Lesions In Thsupporting
confidence: 58%
“…There are currently few studies on the antiulcer action of flavonoids (luteolin, hyperoside) [4,16] polyphenols (paeniflorine, albiflorine), and phenolcarboxylic acids (chlorogenic acid, caffeic acid, rosmarinic acid) [3,43,56]. To quantify these effects on the decrease in gastric secretion and the increase in defence factors (endogenous prostaglandins), numerous studies have evaluated extracts standardized in phytocompounds [28]; thus, various methods of producing experimental ulcers have been developed -by ligation of the pylorus, by administration of reserpine, indomethacin or HCl/ethyl alcohol or by induction of stress ulcer; in all cases, the experimental animal used is preferably the rat. The present study aims to evaluate the antiulcerous potential of the hydroalcoholic extract of the spiciform inflorescence of the species Prunella vulgaris L. due to the high content of active ingredients [5,32,39,40,[45][46][47]52].…”
Section: Introductionmentioning
confidence: 99%
“…(4) QOUH [21]: after treatment, the mucosal changes at the ulcer were observed under the endoscope, to evaluate the maturity of the regenerated mucosa. Two mucosal tissues were taken from the center of the scar for hematoxylin-eosin (HE) staining, and routine pathological observation was performed to evaluate the histological maturity of the regenerated mucosa 2.5.…”
Section: Outcome Measuresmentioning
confidence: 99%